Effect of roasting soybeans and corn on dairy calf performance - I.E.O. Abdelgadir; J. L. Morrill; A. M. Feyerherm; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1993)
To evaluate the effect of roasting soybeans and corn on performance of young dairy calves, newborn Holstein calves (n= 132) were blocked by sex and birth date and randomly assigned to one of six isonitrogenous calf starters. The starters were formulated using soybean meal or soybeans roasted at 280 or 295 °F. Each of these protein sources was used with either raw corn or corn roasted at 280°F. Diets were offered ad libitum from .5 to 8 wk of age. Calves were fed milk at 4% of birth weight twice daily and weaned when they consumed 1.5 lb of starter per day for 3 consecutive days. Soybeans roasted at 295 °F resulted in improved overall calf performance. Roasted corn enhanced performance of calves fed soybean meal but did not alter performance of those fed soybeans roasted at 280 °F and depressed performance of calves fed soybeans roasted at 295 °F. These effects were more pronounced during the postweaning period (6 to 8 wk). These results demonstrate the importance of nutrient interactions in young dairy calves, especially when processed grains are fed.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Dairy calves; Starters; Soybeans; Corn; Roasting